Ear and Hearing Disorders in Representative Sample of Grade-one School Children in Phayao Municipality - Kovjiriyapan, Kanokrot (Journal of Health Science of Thailand, 2017)
The objective of this survey research was to find out the prevalence and cause of hearing impairment among children of school-entry age, in the municipal area of Amphoe Mueang Phayao. This research included 399 children studying in the first year of government school in municipal area.They were examined using otoacoustic emissions and otoscopy. Children with ear disease or hearing impairment were re-examined to find out the type of hearing impairment and treatment. The data were presented in terms of means and percentage. The result showed that impacted wax was found to be the most common cause of ear disease (24.8%) and hearing impairment was detected in 8 children (2%). On retesting, it was predominantly sensory neural hearing loss, observed among 6 out of the 8 children. Hearing screening programe in Thailand should be concerned about early detection and management of common ear disease and hearing impairment and to promote self hygiene practice for ears among school children.